POLA KOMUNIKASI PENGAJAR TERHADAP SANTRI BARU DI PESANTREN - Hasbiyah, Desi; Apriliani, Afmi (JURNAL KOMUNIKATIO, 2021)
Pesantren is an Islamic educational institution with a boarding or boarding system. With the levels of Santri who register at the pesantren come from various ages, the santri teachers must have the ability to communicate and treat so that the students are able to adapt to new habits in pesantren education. This research was conducted to explore the forms of interaction and communication of the teachers as an effective method of delivering messages to the new students. The type of research used in this research is qualitative research, with the case study method. Data collection techniques through participant observation, in-depth interviews, and documentation. The results showed that age is a very important factor in communication to shape perceptions, values, cultural backgrounds, knowledge, roles and the environment that have a high influence on the effectiveness of delivering messages that can create the desired communication. So that the method of delivering effective messages by the teachers to the new students is through the Parenting communication pattern approach using: 1) Permissive communication patterns (tend to behave freely) but remain focused and under supervision, 2) take an approach based on parenting with implementing the concept of reward and punishment ala Rasulullah SAW. With the results of this research, it is hoped that it will become an additional reference for teachers who are responsible for the new santri class to learn parenting and communication as the basis for the ability to convey messages so that the vision and mission of the pesantren can be realized, namely creating the nation's generation.